The Scourge of Poliomyelitis in Pakistan: Barrier towards its eradication - Aisha Mehnaz (Journal of the Pakistan Medical Association, 2024)
Poliomyelitis is an extremely disabling disease caused bythe polio virus, a virus belonging to Picornaviridae family.Humans are the only natural host. The virus principallyinvolves the motor neurons resulting in permanentasymmetrical lifelong paralysis. Effective vaccines areavailable for its eradication. Unfortunately despite vaccineavailability the disease cannot be eradicated from earth yet.Pakistan and Afghanistan are the only two nationsharbouring the polio virus. Lately sporadic cases ofPoliomyelitis have also been reported from countries likeMozambique, which had an outbreak following importingof wild poliovirus (WPV1) from Pakistan.1 As long as a singlechild remains infected, children in all countries are at riskof contracting polio.2 Expanded Programme for Immunization (EPI) was initiatedin Pakistan in 1978. Polio vaccine was included along withfive other vaccines against life threatening diseases likeTuberculosis, Diphtheria, Pertussis, Tetanus, and Measles.The journey that took off smoothly with over 50% vaccinecoverage by 1990 raised to 80% coverage by 2007, hastaken a sharp dip in the ensuing decades. Pakistanunfortunately never recovered from the scourge of poliodisease. In 1988 Global Polio Eradication Initiative (GPEI)was started, that resulted in a decline to 99% cases of polioin the world, but Pakistan continued to face challengeswhich has prevented total eradication of polio.3 Continued...